(untitled) (Ameghiniana, 2021)
Taphonomic studies were carried out at Laguna Flecha Negra locality (Bah a Laura Complex, Middle–Late Jurassic), Santa Cruz Province, Argentina. Sedimentary facies and preservational styles were defined to recognize plant taphofacies in the studied sequence. Eleven taphofacies were identified and plant sources within a volcanic and geothermal system are proposed. Plant remains are of autochthonous to para-autochthonous origin and best preservation was found in distal facies of siliceous hot spring (sinter) systems. Lateral and vertical taphonomic differences were found in the studied sequence. These are due to changes in the sedimentary input and distance to the geothermal fluids. Results enable the reconstruction of the depositional history of this region of the Deseado Massif geological Province. We infer formation of a hot-spring (sinter) system that was subsequently destroyed by a phreatic eruption process at the margin of an andesitic effusive dome in partially reworked fall pyroclastic subfacies. After the destruction of the geothermal system, a fluvial and lacustrine epiclastic subfacies developed preserving a plant community typical of the Middle‒Late Jurassic of Gondwana. Later, volcanic activity produced pyroclastic subfacies, with thick ash-fall and flow deposits from different sources and separated by a time gap that promoted fossilization of an in situ forest. Taphonomic studies of these plant communities allowed reconstruction of a chain of geological events and how these processes have influenced the preservation of a Jurassic flora from Patagonia, thus contributing to an understanding of the paleoecology of the Deseado Massif geological province.